Use of Simulation to Measure the Effects of Just-in-Time Information to Prevent Nursing Medication Errors: A Randomized Controlled Study. Issue 6 (December 2021) - Berg, Thomas A.; Hebert, Susan H.; Chyka, Deb; Nidiffer, Stephanie; Springer, Cary
Abstract : Introduction: Medication administration error (MAE) is the improper dispensing of medication. It is a significant contributor to the occurrence of medical errors. A novel systems thinking approach using a pediatric simulation and student nurses were used to evaluate the benefit of applying just-in-time information (JITI) to reduce medication errors. Just-in-time information applies highly focused information delivered when needed. Methods: A smart device app was developed to provide JITI medication administration information. The effect JITI had on MAE occurrence was assessed via a controlled study. The study population included 38 teams having 2 to 3 senior nursing students on each team. The teams were separated into a control and 2 intervention groups to complete a medication administration simulation. Results: The intervention groups (100%, N = 10) that made significant use of the JITI app demonstrated improved performance for medication administration over the control group. Familiarity with the app was pivotal to how frequently it was used and to the success of the groups in administering medications. Although those with access to the app having limited training successfully executed the simulation 27.3% (n = 11) of the time, those with extended training had a success rate of 77.8% (n = 9). Conclusions: Providing JITI significantly reduced the occurrence of MAEs for these student nurses. Familiarity with the app, including extended training opportunities, contributed significantly to student success. Abstract : Supplemental digital content is available in the text.